Pengembangan Multimedia Interaktif DIGITAX (Digital Tax Administration Media) Berbasis Web Menggunakan Google Sites pada Mata Pelajaran Administrasi Pajak Kelas XI SMK - Putri, Dhiny Avriliamin; Pratiwi, Vivi (Jurnal Pendidikan Akuntansi (JPAK), 2022)
This study aims to create a learning device product for class XI Tax Administration subjects in the form of interactive multimedia based on a website which is expected to have a good feasibility and level of effectiveness. This product is called DIGITAX (Digital Tax Administration Media). This research is a development research with the ADDIE model covering analyze, design, development, implementation, and evaluation. Product testing was carried out at SMK Ketintang Surabaya in class XI AKL 1 with a total of 20 students. The results of the study showed that the validation of the material and media experts obtained very feasible criteria. The student's response obtained very good criteria. So it can be concluded that web-based interactive multimedia learning media in Tax Administration subjects is very feasible to be applied as a medium in online and conventional learning activities.